2018
DOI: 10.7150/jbji.27840
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Tissue and Sonication Fluid Sampling for the Diagnosis of Fracture-Related Infection: A Systematic Review and Critical Appraisal

Abstract: Introduction: Intraoperatively obtained peri-implant tissue cultures remain the standard for diagnosis of fracture-related infection (FRI), although culture-negative cases may complicate treatment decisions. This paper reviews the evidence on sonication fluid and tissue sampling for the diagnosis of FRI.Methods: A comprehensive search in Pubmed, Embase and Web-of-Science was carried out on April 5, 2018, to identify diagnostic validation studies regarding sonication fluid and tissue sampling for FRI.Results: O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 30 publications
4
35
0
3
Order By: Relevance
“…All of the patients had a follow-up for at least one year, and none of them had a clinical relapse of the infection. This is in line with other studies that have reported positive cultures in 28.7% of cases with presumptive aseptic nonunions [ 19 ]. Amorosa et al [ 19 ] reported that 7 patients of the total 15 with positive cultures underwent a secondary operation.…”
Section: Discussionsupporting
confidence: 93%
“…All of the patients had a follow-up for at least one year, and none of them had a clinical relapse of the infection. This is in line with other studies that have reported positive cultures in 28.7% of cases with presumptive aseptic nonunions [ 19 ]. Amorosa et al [ 19 ] reported that 7 patients of the total 15 with positive cultures underwent a secondary operation.…”
Section: Discussionsupporting
confidence: 93%
“… 32 Prior studies reported sonication fluid sensitivity for FRI at between 65% and 95%, with specificity between 50% and 97%. 33 Sonication should be used together with deep tissue sampling for optimum diagnostic accuracy. 28 , 32 …”
Section: Microbiological Diagnosis Of Frimentioning
confidence: 99%
“… 8 The reason for this was the lack of clear scientific evidence and, more specifically, agreement on a cut-off value above which FRI can be reliably diagnosed. 8 , 33 …”
Section: Histopathologymentioning
confidence: 99%
“…However, the exact conditions and mechanisms underlying the VNBC concept remain to be fully understood, but do represent a possible risk in ODRI studies. To maximize chances of accurate culture results, adopting clinical methods towards improved isolation and culture of biopsies should also be considered, that is, sonication of biopsies and associated hardware components or the use of known biofilm‐dispersing agents during sample processing …”
Section: Bacteriological Aspects Of Odri Studiesmentioning
confidence: 99%